Influence of silica fume addition on selected properties of fine-grained concrete = Wpływ dodatku mikrokrzemionki na wybrane właściwości betonu drobnoziarnistego - Denisiewicz, Arkadiusz; Kula, Krzysztof; Socha, Tomasz; Kwiatkowski, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of laboratory tests of selected mechanical and physical properties of fine-grained concrete. The tests were carried out on samples with varying degrees of microsilica addition. The consistency class, shrinkage, compressive and bending strength, water resistance and frost resistance were determined for the designed concrete mixtures and made samples.
Keywords: silica fume; fine-grained concrete; laboratory tests; pył krzemionkowy; beton drobnoziarnisty; badania laboratoryjne